Sphingolipids in Lung Pathology in the Coronavirus Disease Era: A Review of Sphingolipid Involvement in the Pathogenesis of Lung Damage - Khan, Saad A.; Goliwas, Kayla F.; Deshane, Jessy S. (Frontiers in Physiology, 2021)
Sphingolipids are bioactive lipids involved in the regulation of cell survival, proliferation, and the inflammatory response. The SphK/S1P/S1PR pathway (S1P pathway) is a driver of many anti-apoptotic and proliferative processes. Pro-survival sphingolipid sphingosine-1-phosphate (S1P) initiates its signaling cascade by interacting with various sphingosine-1-phosphate receptors (S1PR) through which it is able to exert its pro-survival or inflammatory effects. Whereas sphingolipids, including ceramides and sphingosines a pro-apoptotic. The pro-apoptotic lipid, ceramide, can be produced de novo by ceramide synthases and ¬converted to sphingosine by way of ceramidases. The balance of these antagonistic lipids and how this balance manifests is the essence of the sphingolipid rheostat. Recent studies on SARS-CoV-2 have implicated the S1P pathway in the pathogenesis of novel coronavirus disease COVID-19-related lung damage. Accumulating evidence indicates that an aberrant inflammatory process, known as “cytokine storm” causes lung injury in COVID-19, and studies have shown that the S1P pathway is involved in signaling this hyperinflammatory response. Beyond the influence of this pathway on cytokine storm, over the last decade the S1P pathway has been investigated for its role in a wide array of lung pathologies, including pulmonary fibrosis, pulmonary arterial hypertension (PAH), and lung cancer. Various studies have used S1P pathway modulators in models of lung disease; many of these efforts have yielded results that point to the potential efficacy of targeting this pathway for future treatment options. Additionally, they have emphasized S1P pathway’s significant role in inflammation, fibrosis, and a number of other endothelial and epithelial changes that contribute to lung damage. This review summarizes the S1P pathway’s involvement in COVID-19 and chronic lung diseases and discusses the potential for targeting S1P pathway as a therapeutic option for these diseases.